Pharmaceuticals in treatment of oral mucosal manifestations of manifestations of various diseases on the oral mucosa - Irina K. Lutskaya (LLC "MEDIAFORMAT", 2021)
The paper reports principles for etiotropic and symptomatic therapy of oral mucosal diseases. The options for dental care tactics selection by the general practitioner, the primary care physician, based on the clinical manifestations are discussed using certain nosological entities as examples. It has been shown that general functional state of the organism plays a vital part in achieving treatment efficacy.